Successful treatment of PGAD/GPD with leuprolide: a case report - Wang Rong; Wang Rong; Hongwen Zhou; Hongqi Fan (Frontiers in Psychiatry)
Persistent genital arousal disorder/genitopelvic dysesthesia (PGAD/GPD) is a rare clinical condition of uncertain etiology. It is characterized by involuntary genital arousal occurring in the absence of sexual interest or desire, and may be accompanied by abnormal sensations in the pelvic and reproductive regions. PGAD/GPD exerts a profound negative impact on patients’ physical and mental health, severely impairing daily functioning and, in some cases, leading to suicidal ideation. This case highlights the potential role of COVID-19 as a triggering factor in the development of PGAD/GPD. The marked improvement in symptoms following treatment with leuprolide suggests that dysregulation of gonadotropin/GnRH signaling may constitute a key pathogenic mechanism underlying this condition. We anticipate that this successful treatment case will provide valuable insights into the etiology and treatment strategies of PGAD/GPD.